THE QUALITY OF ADVOCACY SERVICES FOR FEMALE VICTIMS OF PSYCHOLOGICAL VIOLENCE AT THE OFFICE OF WOMEN'S EMPOWERMENT AND CHILD PROTECTION OF HULU SUNGAI UTARA REGENCY - Naya Afifatul Zahra; Siti Raudah; Norhidayah (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
Psychological violence experienced by women has serious impacts on their mental state, social condition, and overall well-being, necessitating effective advocacy services from government agencies. This study aims to determine the quality of advocacy services for female victims of psychological violence at the Office of Women's Empowerment and Child Protection of Hulu Sungai Utara Regency. This research utilizes a qualitative method with a descriptive approach. Data collection was conducted through interviews, observations, and documentation, involving advocates and female victims of psychological violence as informants. Data analysis techniques were carried out through data reduction, data presentation, and conclusion drawing.The results indicate that the advocacy services provided have performed reasonably well based on service quality indicators, including aspects of tangibles, reliability, responsiveness, assurance, and empathy. However, several obstacles were identified during implementation, such as limited human resources, inadequate supporting facilities, and uncertainties regarding the understanding of applicable Standard Operating Procedures (SOPs). Therefore, improvements in service quality are required through capacity building for advocates and the optimization of supporting facilities to ensure maximum protection for women victims of psychological violence.